Influencia de la aplicación del programa EDA “Estrategias didácticas activas” en el mejoramiento de la comprensión lectora de los alumnos del 6to grado “C” de la I.E N°00744 Santo Toribio - Calderón Barturen, Medin (2011)
The Act of reading is more than decoding the meaning of words or find main ideas in a written text, is a gradual and continuous process that lasts a lifetime and develops according to the different types of texts; Therefore, it is essential that the learning to read be evaluated at its various stages. The proper handling of written texts of greater complexity involves learning new skills from reading. The activity reading is sees reduced to when is subject to make questions literal on the content of a text, believing that with this them students manage to assimilate it reading ~ accordingly, not is allows that them children is face to the text using their skills of reading, inference, and analysis critical, this cbnlleva to consider that the make questions is more a maQ ~ ra of assess that of teach to understand. According to DELGADO et al. (2005, p. 54), "reading is, in the process-. Educational, an element Basic for the development d...